Psychosomatically oriented diagnostics and therapy for fertility disorders: guideline of the DGPFG (S2k-level, AWMF registry number 016/003, December 2019) = Psychosomatisch orientierte Diagnostik und Therapie bei Fertilitätsstörungen : Leitlinie der DGPFG (S2k-Level, AWMF-Registernummer 016/003, Dezember 2019) - Wischmann, Tewes; Borkenhagen, Ada; David, Matthias; Dorn, Almut; Dorn, Christoph; Gagsteiger, Friedrich; Goeckenjan, Maren; Ludwig, Annika Kristin; Meier-Credner, Anne; Röhrig, Michelle; Rothe-Kirchberger, Ingrid; Schick, Maren; et al. (Geburtshilfe und Frauenheilkunde, 2021)
Aim The purpose of this official guideline published and coordinated by the German Society for Psychosomatic Gynecology and Obstetrics [Deutsche Gesellschaft für Psychosomatische Frauenheilkunde und Geburtshilfe (DGPFG)] is to provide a consensus-based overview of psychosomatically oriented diagnostic procedures and treatments for fertility disorders by evaluating the relevant literature. Method This S2k guideline was developed using a structured consensus process which included representative members of various professions; the guideline was commissioned by the DGPFG and is based on the 2014 version of the guideline. Recommendations The guideline provides recommendations on psychosomatically oriented diagnostic procedures and treatments for fertility disorders.